2004
DOI: 10.1001/archpedi.158.6.515
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Assessment of Quality of Care and Grief Following a Child's Death

Abstract: Although there were some differences in grief responses among parents, satisfaction-with-care scores were high. Further studies should examine the role of satisfaction with care in parental grief response and incorporate the reporting of experiences rather than simple ratings to measure satisfaction with care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 34 publications
1
46
0
3
Order By: Relevance
“…In addition, other studies have found that multiple factors predict parental grief, including the length of the child's illness, parent's history of previous losses and whether the child's death was anticipated. 21,22 In the current study, grief scores did not differ significantly between parents who had hospice or palliative care involvement and those parents who did not have these services. Due to the small sample size of the current study, we were not able to determine if this or other factors contributed to the grief level in this group of parents.…”
Section: Discussionmentioning
confidence: 44%
“…In addition, other studies have found that multiple factors predict parental grief, including the length of the child's illness, parent's history of previous losses and whether the child's death was anticipated. 21,22 In the current study, grief scores did not differ significantly between parents who had hospice or palliative care involvement and those parents who did not have these services. Due to the small sample size of the current study, we were not able to determine if this or other factors contributed to the grief level in this group of parents.…”
Section: Discussionmentioning
confidence: 44%
“…[20][21][22] A few studies have examined satisfaction among families undergoing prenatal diagnosis, but none have linked satisfaction or dissatisfaction with specific aspects of care. This study adds to our knowledge by identifying aspects of care that are key in determining satisfaction and could be targeted to optimize family satisfaction with care: expressions of empathy from provider, continuity of care, communication, valuing the fetus and developing care plans.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] This unique pilot study reports and compares the experiences of neonatologists, advanced practitioners, nurses, and parents at a single-center level III and level IV NICU without a formal palliative care team. While the parent and healthcare team surveys represent two slightly different time periods, the low turnover rates for neonatologists, advanced practitioners, and nurses and the absence of significant changes in practice may indicate that care was consistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, data specific to NICU setting are limited. [18][19][20][21][22][23][24][25][26] Furthermore, no study to date has described multiple stakeholders' perspectives of end-of-life experiences in this setting.…”
mentioning
confidence: 99%